Alternative disclosing solution from natural materials: Bahan disclosing solution alternatif dari bahan alami - Putri, Elphira Darma; Pratiwi, Chika Indah; Dirgantara, Difa; Irzal, Embun; Adhani, Falladira; Ilmi, Qoriatul; Surya, Leny Sang (Makassar Dental Journal, 2024)
Disclosing solution is a dye that can change the colour of dental plaque to contrast with the colour of the tooth surface. Dental plaque has the ability to retain dyes due to the difference in polarity between plaque components and dyes. This review discusses alternative DS materials from natural materials. Using literature review, the researchers found 108 articles that matched the key-words, then screened based on duplication, title, and abstract. Eleven articles that met the inclusion criteria and theme. Nine of the 11 selected studies stated that these natural ingredients have potential in identification. It was concluded that many natural in-gredients are effective as alternatives to DS, including beetroot, mulberry juice, red dragon fruit, purple sweet potato, ethanol extract of inai leaves, combination of beetroot extract and VCO, rosella petal extract, senduduk fruit and red dragon fruit peel.